EVALUASI SIFAT FISIK PATI GANYONG (Canna edulis Kerr.) SEBAGAI BAHAN BAKU PEMBUATAN KWETIAW PADA TINGKAT SUBSTITUSI YANG BERBEDA - MURNA MUZAIFA '; MUHAMMAD IKHSAN SULAIMAN; LIYUZA ' ' (Jurnal Sagu, 2014)
Canna is an alternative carbohydrate sources that have not been developed yet. With a fairly high carbohydratecontent, ganyong can be used as industrial raw materials.The aim of this research was to evaluate physicalproperties of canna starch as raw material on kwetiaw production with different substitution level. Thisstudy was conducted using randomized completely design with single factor, the persentation of cannastarch which consist of 5 levels : A = 0%, B = 25%, C = 50%, D = 75% and E = 100%. Experimental datawere subjected to ANOVA test followed by LSD with 1% level of significance. Parameter analyzed wereswelling power, viscosity, freeze-thaw stability (% sineresis) and paste clarity. The result showed that swellingpower, degradation viscosity, freeze-thaw stability and paste clarity were increased with increasing of cannastarch persentation.Key words: canna starch, kwetiaw, swelling power, viscosity